Viral Loads and Immunities: Reflecting on Neoliberalism, Motherhood, and Academia during the COVID-19 Pandemic - Kisitu, Alexandra (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
This creative, reflection paper explores neoliberalism in academia and motherhood, and it speaks from my position as a thirty-three-year-old mother of two young children (aged six and four) and as an ABD (all but dissertation) graduate student in sociology and women’s studies. My family and I currently live in the Twin Cities metro area of Minnesota. I am a white (Irish and Lebanese), and my husband is Black (from Uganda). I grew up in a single-parent household and my husband, who grew up in Uganda, was orphaned at a very young age. Though different in terms of our social environments, we both experienced debilitating poverty as children. As the pandemic ravages on and instability becomes familiar to us yet again, I explore the precarious situation of being captured in the neoliberal pressures of education and motherhood while attempting to artistically and intuitively explore spaces outside of these realms to better my relationship with my work, my children, my body, my partner, and myself. I explore these concepts alongside the COVID-19 pandemic and how the entanglements of neoliberalism, work, motherhood, academia, and racism intersect in my family’s lives. I also explore the role mothers (myself included) have in supporting family health, as well as the outside pressures, that create tension in the achievability of optimal family health and wellness. I explore these issues context of the current pandemic and the current racial and political climate in the United States as I raise my mixed race children during this time.